OP0132 Remission According to the ACR/EULAR Remission Criteria in Patients with Early Arthritis is Significantly Influenced by Patient-Reported Fatigue and Well-Being. (23rd January 2014) - Callhoff, J.; Westhoff, G.; Edelmann, E.; Schett, G.; Schneider, M.; Zink, A.
Abstract : Background: The course of early inflammatory arthritis (IA) is influenced by many factors. The use of DMARDs and glucocorticoids may change the progression of the disease. Besides that, the probability of a patient reaching remission within the first year may also be influenced by general physical and psychological well-being. Objectives: To investigate which clinical and patient-reported parameters predict clinical remission at 12 months according to three commonly used remission criteria. Methods: Remission according to the 3 most common definitions ACR/EULAR-remission, Disease Activity Score (DAS28) <2.6, and Simplified Disease Activity Index (SDAI) <3.3 was evaluated in 700 patients from an early IA (<6 months) cohort. Multivariate logistic regression analyses were used to identify baseline parameters associated with remission. Analyses were adjusted for age, sex, education, body mass index (BMI) and cardiovascular comorbidities. The predictive value of smoking (never, past, current), use of glucocorticoids and DMARDs at baseline (yes/no), acute phase reactants (CRP, ESR), numbers of swollen/tender joints (0-28) and teeth (0-28), patient global health (VAS 0-10), fatigue (5 PROFAD dimensions, 0-50, no to extreme fatigue), physical function (FFbH, 0 -100; no to full function) and the RA Impact of Disease score (RAID, 0-10; no to extreme impact) was analyzed. Results: Patients were 57±14 years old and had symptom duration of 13±7 weeks at study entry, 64% were female. At 12 months, 18% of the patients were in ACR/EULAR remission, 18% in SDAI remission, and 47% in DAS28 remission. 48% of the patients fulfilled at least one of the remission criteria, 10% fulfilled all three. In adjusted multivariate logistic regression models only patient reported outcomes, namely functional capacity, disease impact (RAID) and several dimensions of fatigue (PROFAD) were predictive of being in ACR/EULAR remission, no clinical baseline parameters were significantly associated. For SDAI remission, in addition to the PROs mentioned above, use of glucocorticoids at baseline significantly improved the chance of achieving remission. For DAS28 remission, also functional capacity, patient global health, number of teeth and use of glucocorticoids were significantly associated. Image/graph: Conclusions: In early IA patients, the chance of being in ACR/EULAR or SDAI remission at 12 months is influenced more by functional capacity, fatigue and physical as well as psychological well-being than by clinical disease activity parameters such as the acute phase reactants. These do play a role for predicting DAS28 remission, though. Our data show that the three remission criteria differently reflect disease activity, treatment and patient reported dimensions of disease severity. From a patient perspective, remission according to the ACR/EULAR or SDAI criteria might be more relevant than remission according to the DAS28 cutoff. Disclosure of Interest: None Declared